MIRU-VNTR analysis of Mycobacterium tuberculosis from Tehran, Sistan-Baluchestan, Kermanshah and Hormozgan during 2014 and 2015 - Baghbanian, Mahroo; Zandi, Hengameh; Zamani, Samin; Javadpour, Sedigheh; Hamzehloo, Gholam Reza; Feizabadi, Mohammad Mahdi (Cellular and Molecular Biology, 2017)
Standard 15-locus Mycobacterial Interspersed Repetitive Unit Variable Number Tandem Repeat (MIRU-VNTR) typing of Mycobacterium tuberculosis (MTB) is a valuable instrumentation for TB control. Our knowledge about the genetic diversity of MTB and population structure of MTB circulating in Iran is limited. During 2014–2015, 98 MTB isolates were collected from the TB centers of four provinces of Iran. Isolates were genetically characterized using 15-locus based MIRU-VNTR typing. Ninety-five distinct mycobacterial interspersed repetitive unit MIRU-VNTR patterns were found among 98 isolates. 5 (5.1%) isolates grouped into 2 clusters and 93 (94.89%) isolates had a unique pattern. The HGDI was as high as 0.99 and 10 of loci were designated as highly discriminative. Clusters belonged to Tehran only. This indicates these patterns are rotating in Tehran. Unique patterns suggest that distribution of samples in each province and population differs. HGDI is higher than previous studies for MIRU-VNTR typing in Iran. We suggest MIRU-15 because it is a valid epidemiological background for clustering defined. Limited data is available on the genetic diversity and transmission dynamics of MTB in Iran. To examine the genetic diversity and transmission dynamics of MTB strains we genotyped a collection of isolates from four different parts of Iran. The method of 15-loci MIRU-VNTR demonstrated high discriminatory power and may be applied as a first-line genotyping instrumentation in investigating the molecular epidemiology of M. tuberculosis in Iran.